Pentingnya Pendidikan Karakter di Sekolah - Hazizah Isnaini; Robie Fanreza (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
A serious problem faced by the Indonesian people is the orientation of the current education system which focuses too much on developing the left brain (cognitive) and pays too little attention to developing the right brain (affective, empathy and feeling). The learning process is passive and rigid, which makes it unpleasant for children. Subjects related to character education (such as character and religion) emphasize the left brain aspect (memorization, or just knowledge) in practice. This can damage children's character and hinder their creativity. In fact, character formation must be carried out systematically and continuously involving aspects of knowledge, feeling, loving and acting. Character formation can be likened to the formation of a person into a body builder (bodybuilder) who requires continuous moral muscle training to become sturdy and strong. Apart from that, the success of character education must also be supported by a good and enjoyable educational environment for children. Character education is needed not only at school, but also at home and in social environments.